Etnomatematika dalam kerajinan peralatan dapur berbahan limbah di Desa Ohoitahit Kota Tual - Muhamad Tahir Rahakbau; Djaffar Lessy; Patma Sopamena (IKIP Siliwangi, 2026)
Mathematics in school is often viewed as abstract and less relevant to students' daily lives. Therefore, a contextual approach is needed that connects mathematical concepts to the local culture of the community. This study aims to examine ethnomathematics in aluminum kitchenware crafts in Ohoitahit Village, Tual City. This study uses a qualitative method with an ethnographic approach to uncover the mathematical concepts integrated into the practice of making traditional kitchenware. The results show that the Ohoitahit community intuitively applies mathematical activities such as counting, localizing, measuring, designing, playing, and explaining in every stage of production. This mathematical knowledge is passed down orally and empirically, becoming an integral part of the community's culture. This study emphasizes the importance of ethnomathematics as a tool for understanding local wisdom and developing more relevant and contextual mathematics education.